Interacción entre los residuos de plaguicidas en uva y el proceso de vinificación - Turaglio, María Eugenia; Navarro, Rosanna Graciela; Becerra, Violeta Cristina; Sari, Santiago Eduardo; Perez, Maria Dolores (EEA Mendoza, INTA, 2024)
EEA Mendoza